State Sukuk Regulation and Strategies for Market Growth in Indonesia - Mulyati, Desi Eka (Islamicate Institute, 2024)
This study analyzes the regulation of State Sharia Securities (SBSN) in Indonesia and explores strategies for sukuk market development. Anchored in Law No. 19/2008, SBSN plays a vital role in financing infrastructure and diversifying sovereign financing. Using qualitative and normative methods, this article reviews legal instruments, fatwas, and institutional policies, along with scholarly and institutional literature. Findings reveal that while sukuk issuance has grown significantly, challenges remain in legal harmonization, tax treatment, investor protection, liquidity, and awareness. Comparative insights suggest Indonesia must strengthen its regulatory clarity, secondary market infrastructure, and product diversity to match global peers. Policy recommendations include establishing a Sukuk Development Agency, harmonizing regulations, introducing benchmark sukuk, promoting retail and green sukuk, and enhancing international integration. This study contributes theoretically to sovereign sukuk regulation discourse and practically to policymaking in Islamic finance.